[Sárga csillaggal megjelölt zsidók meneteltetése Budapesten, 1944] (Hungary, 1944)
Newsreel by an unknown military man documenting the abuse of Jews in Budapest. The group consists of mostly women, children and elderly men, marching in a row, hands up, wearing yellow stars as a stigma, at Rákóczi street.
Slow motion and
Keywords: Newsreels